Transcriptomic analysis of Campylobacter jejuni NCTC 11168 in response to epinephrine and norepinephrine - Xu, Fuzhou; Wu, Cun; Guo, Fangfang; Cui, Guolin; Zeng, Ximin; Yang, Bing; Lin, Jun (Frontiers in Microbiology, 2015)
Upon colonization in the host gastrointestinal tract, the enteric bacterial pathogen Campylobacter jejuni is exposed to a variety of signaling molecules including the catecholamine hormones epinephrine (Epi) and norepinephrine (NE). NE has been observed to stimulate the growth and potentially enhance the pathogenicity of C. jejuni. However, the underlying mechanisms are still largely unknown. In this study, both Epi and NE were also observed to promote C. jejuni growth in MEM-based iron-restricted medium. Adhesion and invasion of Caco-2 cells by C. jejuni were also enhanced upon exposure to Epi or NE. To further examine the effect of Epi or NE on the pathobiology of C. jejuni, transcriptomic profiles were conducted for C. jejuni NCTC 11168 that was cultured in iron-restricted medium supplemented with Epi or NE. Compared to the genes expressed in the absence of the catecholamine hormones, 183 and 156 genes were differentially expressed in C. jejuni NCTC 11168 that was grown in the presence of Epi and NE, respectively. Of these differentially expressed genes, 102 genes were common for both Epi and NE treatments. The genes differentially expressed by Epi or NE are involved in diverse cellular functions including iron uptake, motility, virulence, oxidative stress response, nitrosative stress tolerance, enzyme metabolism, DNA repair and metabolism and ribosomal protein biosynthesis. The transcriptome analysis indicated that Epi and NE have similar effects on the gene expression of C. jejuni, and provided insights into the delicate interaction between C. jejuni and intestinal stress hormones in the host.